The Student’s Psychological Stress During Covid-19: Stres Psikologis Siswa Selama Covid-19 - Qabila Ibrahim Hasan (Academia Open, 2024)
This study investigates psychological stress among middle school students in Baquba district during the COVID-19 pandemic, focusing on potential gender-based differences. Despite established evidence of heightened stress levels during pandemics, few studies have explored these impacts on school-aged children and potential variances between genders. Utilizing a balanced sample of 100 students (50 male and 50 female) from four schools, this research employed a psychological stress scale with confirmed psychometric properties, including a stability coefficient of 0.80. Statistical analysis revealed significant stress levels among the students, yet no gender differences were identified at the 0.05 significance level. These findings suggest that interventions aimed at reducing student stress during pandemics need not differentiate between male and female students but should instead focus on strategies that address the broader student population. Highlights: Significant psychological stress exists among middle school students during COVID-19. No statistical difference in stress levels between male and female students. Stress reduction interventions should target all students, regardless of gender. Keywords: Psychological Stress, COVID-19, Gender Differences, Middle School, Stress Interventions